تأثير الاستثمار الأجنبي المباشر على الدخل الاستهلاكي في الجزائر - دراسة قياسية للفترة (1990- 2021) باستعمال دالة الاستثمار الكينزية - - طالب, محمد الأمين وليد; جفافلة, عبد العالي (جامعة الوادي - University of Eloued, 2023)
The study aims to show the relationship between foreign direct investment and consumer income in Algeria. The study relied on statistics issued by the United Nations, in addition to the publications of the Algerian National Bureau of Statistics. It has adopted the descriptive approach and the analytical approach. As the standard study during the period 1990-2021 showed that the relationship between foreign direct investment and the income of the consumer sector in Algeria is very weak; This is based on the Keynesian investment function, which showed that the marginal propensity for foreign direct investment in Algeria, depending on consumer income, is estimated at 2.05%, meaning that the increase in consumer income by one unit is offset by an increase in foreign direct investment by 0.0205 units, and this is a weak indicator indicating that there is no strong relationship. Between foreign direct investment in Algeria and consumer income during the period 1990-2021, we find periods in which consumer income maintained the same level of rise with a decrease in the flow of foreign direct investment.
The impact of foreign direct investment on consumer income in Algeria - An econometric study for the period (1990-2021) using the Keynesian - function invest
مقال
Keywords: الاستثمار الأجنبي المباشر ; الدخل الاستهلاكي ; دراسة قياسية ; الجزائر: Foreign direct investment, consumer income, an econometric study, Alger